Bottom Mixing Enhanced by Tropical Storm‐Generated Near‐Inertial Waves Entering Critical Layers in the Straits of Florida. Issue 15 (6th August 2021) - Qu, Lixin; Thomas, Leif; Gula, Jonathan
Abstract: Tropical storms and hurricanes frequently pass over the Straits of Florida, energizing the near‐inertial wave (NIW) field in the strait. Two ship‐based surveys, which were launched shortly after storms, observed velocity shear bands over the western slope of the strait—clear signatures of NIWs. Also, the hydrographic measurements demonstrate the formation of a slantwise critical layer (where isopycnals are parallel with bathymetry) over the western slope, which is known to be a trapping zone for NIWs. A realistic simulation of the Straits confirms the emergence of NIWs under a tropical storm, which is accompanied by inertially modulated bottom‐enhanced mixing over the western slope. The mechanism driving the mixing is that the storm‐generated NIWs radiate downward from the core of the Florida Current, reflect off the eastern slope, and enter the slantwise critical layer over the western slope; upon entering, wave trapping, and amplification lead to the enhanced mixing. Plain Language Summary: Strong winds blowing over the ocean inject a significant amount of energy into the ocean. Some of this energy goes into near‐inertial waves, internal waves radiating from the surface that transmit energy into the ocean interior. Near‐inertial waves (NIWs) are thought to play a role in mixing deep waters and sustaining the global overturning circulation. However, they have not been considered as a key driver of mixing near the seafloor. In this study, we present observations of storm‐generated NIWs over the seafloor of the Straits of Florida by two research cruises launched shortly after tropical storms. Supported by theories, our numerical simulations show supportive evidence that the seafloor mixing in the Straits of Florida can be enhanced by these storm‐generated NIWs. The benthic deep‐water coral ecosystems and the properties of intermediate water masses are potentially influenced by this mixing enhancement. Key Points: A slantwise critical layer for near‐inertial waves is observed over the western slope of the Straits of Florida Signatures of near‐inertial waves are observed in the slantwise critical layer after tropical storms pass over the Straits of Florida Upon entering the slantwise critical layer, the waves are trapped and hence amplified, leading to mixing enhancement over the western slope